Deficiente involucramiento de los Padres de Familia en el proceso académico de los estudiantes de la Unidad Educativa Comunitaria Intercultural Bilingüe ‘MUSHUK RIMAK’ de la Parroquia San Lucas, y la intervención del Trabajador Social - Solano Pérez, Rosa Mercy (2018)
The present investigative work focuses on a study carried out on students, parents and teachers of the Mushuk Rimak Intercultural Bilingual Community Educational Unit of the San Lucas parish of the Loja canton. For the academic process to work in the best way, it is important that there is intervention and full involvement of students, parents, and teachers, because in this way good results will be reflected in the students; It is the fundamental role of the mother and the father of family to be involved in each of the educational aspects of their children. The present investigative work, allowed to know the results on: How does the poor involvement and attention of the parents affect the academic process of the students of the first high school parallel "a" "b" and "c" of the Intercultural Educational Unit Bilingual Mushuk Rimak, aims to theoretically support the categories of analysis of the object of study to support the problem posed to know the causes and consequences that lead to poor involvement and attention of parents in the academic process of their children. The methods used for this correspond to the scientific, inductive, deductive, analytical, synthetic, bibliographic and statistical method, each one applied in its respective field of study. The techniques were direct observation, survey, unstructured interview, and bibliographic review; while the instruments that were used were the observation cards, field notebook, questionnaire, script of the unstructured interview, bibliographic records, photographs. 6 Through observation, as well as the application of the survey directed to the educational trilogy and the conduct of the interview to the authority of the institution, it is alluded to that the results obtained prove that there is a deficient involvement and attention of the parents of the same family has a great influence on the academic process of their children, a negative aspect that demonstrates, demotivation and low academic and social development of adolescents. As a conclusion, the importance of parents' involvement in their children's academic process is highlighted, because even if it does not seem like it is very significant for students, the fact that their parents are aware of them will help them to achieve greater academic development and you will have confident adolescents; the example comes from home and it is the parents who must train their children so that they too are excellent people responsible for their obligations. This is how a social proposal is presented aimed at getting parents fully involved in the academic process of their children, making them feel more committed and interested and understand the importance of their children before their work or other activities.